Cyclic application of transformations using scales for spatially or structurally determined design - Hofmeyer, H. (Automation in construction, 2007)
In multi-disciplinary design processes in the field of Architecture, Engineering, and Construction (AEC), the design of buildings is continuously subject to transformations by the individual disciplines, e.g. when the structural designer makes a structural design for the building using the spatial design of the architect as a starting point. This paper will show that by introducing a scale for evaluating the design stages between the individual disciplines in a cyclic application of transformations, new insights can be obtained into the relationship between spatial and structural design in addition to the overall multi-disciplinary design process. The proposed design stage scale will indicate whether a design is developed to create space (spatially determined) or to create structure (structurally determined). Examples are presented for small-scale buildings and specific transitions. They will show that fundamentals, e.g. diaphragms separate spaces, will automatically be generated by the proposed cyclic application of transformations. The method also allows conclusions to be drawn from the design process, e.g. the spatial design layout will determine whether the ensuing design steps will evolve towards a spatially determined design or towards an integrated design. The idea of cyclic application with evaluation scales can be developed further by applying it to large scale buildings with additional and/or other types of transitions and scales.